Existence of zero-group velocity modes in an incompressible plate - Hussain, T.; Ahmad, F. (Archives of Mechanics, 2014)
Zero-group velocity (ZGV) Lamb modes are studied in an incompressible orthotropic plate. The existence of such modes critically depends on the anisotropy parameter a = (c11 + c22 − 2c12 − 4c66)/c66. With materials having a > −1, none of the modes possesses any ZGV points and every mode has such a point if a < −1. Several modes have multiple ZGV points.